1. ## The Chain Rule

I have this problem:
g(x)=(1+4x)5(3+x-x2)8
and I must find the derivative.

The chain rule states F'(x)=f'(g(x))*g'(x). The chain rule with powers is (un)'=nun-1​(u').

I've tried this problem a thousand different ways (a sure sign I'm doing it wrong) and cannot seem to get the answer. I peeked at the back of the book and found it the answer is g'(x)=4(1+4x)4(3+x-x2)7(17+9x-21x2).

I cannot figure out how and I've been pulling my hair out all weekend. Please help me!

2. Originally Posted by TiPster
I have this problem:
g(x)=(1+4x)5(3+x-x2)8
and I must find the derivative.

The chain rule states F'(x)=f'(g(x))*g'(x). The chain rule with powers is (un)'=nun-1​(u').

I've tried this problem a thousand different ways (a sure sign I'm doing it wrong) and cannot seem to get the answer. I peeked at the back of the book and found it the answer is g'(x)=4(1+4x)4(3+x-x2)7(17+9x-21x2).

I cannot figure out how and I've been pulling my hair out all weekend. Please help me!
Please post what you tried to do so we can see where your mistake lies. That way we can prevent you from doing the same mistake again

3. Originally Posted by TiPster
I have this problem:
g(x)=(1+4x)5(3+x-x2)8
and I must find the derivative.

The chain rule states F'(x)=f'(g(x))*g'(x). The chain rule with powers is (un)'=nun-1​(u').

I've tried this problem a thousand different ways (a sure sign I'm doing it wrong) and cannot seem to get the answer. I peeked at the back of the book and found it the answer is g'(x)=4(1+4x)4(3+x-x2)7(17+9x-21x2).

I cannot figure out how and I've been pulling my hair out all weekend. Please help me!
You also need to apply the Product Rule.
g(x) = u(x) v(x) ---> g'(x) = u'(x)v(x) + u(x)v'(x)

Now apply the power rule and the chain rule to each of the two terms.

Show us your work so we can see where you have gone astray!